Behavioral and Brain Measures of Morphological Processing in Children With and Without Familial Risk for Dyslexia From Pre-school to First Grade - Louleli, Natalia; Hämäläinen, Jarmo A.; Leppänen, Paavo H. T. (Frontiers in Communication, 2021)
School-age reading skills are associated with and predicted by preschool-age cognitive risk factors for dyslexia, such as deficits in phonological awareness, rapid automatized naming, letter knowledge, and verbal short-term memory. In addition, evidence exists that problems in morphological information processing could be considered a risk factor for dyslexia. In the present study, 27 children at pre-school age and the same 27 children at first grade age performed a morphological awareness task while their brain responses were measured with magnetoencephalography. Our aim was to examine how derivational morphology in Finnish language, and concomitant accuracy and reaction times are associated with first grade reading, in addition to the preschool age reading-related cognitive skills. The results replicated earlier findings; we found significant correlations between pre-school phonological skills and first-grade reading, pre-school rapid naming and first-grade reading, and pre-school verbal short-term memory and first-grade reading. The results also revealed a significant correlation between the pre-school children’s reaction time for correctly derived words in the morphological task and the first-grade children’s performance in rapid automatized naming for letters. No significant correlations were found between brain activation measures of morphological processing and first-grade reading.